Candida antarctica Lipase A-Based Enantiorecognition of a Highly Strained 4-Dibenzocyclooctynol (DIBO) Used for PET Imaging - Sirén Saija; Dahlström Käthe M.; Puttreddy Rakesh; Rissanen Kari; Salminen Tiina A.; Scheinin Mika; Li Xiang-Guo; Liljeblad Arto (MDPI AG, 2022)
The enantiomers of aromatic 4-dibenzocyclooctynol (DIBO), used for radiolabeling and subsequent conjugation of biomolecules to form radioligands for positron emission tomography (PET), were separated by kinetic resolution using lipase A from Candida antarctica (CAL-A). In optimized conditions, (R)-DIBO [(R)-1, ee 95%] and its acetylated (S)-ester [(S)-2, ee 96%] were isolated. In silico docking results explained the ability of CAL-A to differentiate the enantiomers of DIBO and to accommodate various acyl donors. Anhydrous MgCl2 was used for binding water from the reaction medium and, thus, for obtaining higher conversion by preventing hydrolysis of the product (S)-2 into the starting material. Since the presence of hydrated MgCl2·6H2O also allowed high conversion or effect on enantioselectivity, Mg2+ ion was suspected to interact with the enzyme. Binding site predictions indicated at least two sites of interest; one in the lid domain at the bottom of the acyl binding pocket and another at the interface of the hydrolase and flap domains, just above the active site.